2017
DOI: 10.1016/j.bbr.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential stress induced c-Fos expression and identification of region-specific miRNA-mRNA networks in the dorsal raphe and amygdala of high-responder/low-responder rats

Abstract: Chronic stress triggers a variety of physical and mental health problems, and how individuals cope with stress influences risk for emotional disorders. To investigate molecular mechanisms underlying distinct stress coping styles, we utilized rats that were selectively-bred for differences in emotionality and stress reactivity. We show that high novelty responding (HR) rats readily bury a shock probe in the defensive burying test, a measure of proactive stress coping behavior, while low novelty responding (LR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 82 publications
6
38
0
Order By: Relevance
“…Alterations in these genes could potentially contribute to the observed HR/LR neurophysiological differences and/or may be involved in known behavioral differences. For instance, recent studies have associated increased expression of GRM5 with positive stress coping and resilience (Piers et al, ; Sun et al, ), so it is conceivable that HR rats' increased GRM5 levels relative to LRs may be associated with their proactive coping styles (Cohen et al, ). Additionally, the increased GRM5 levels in HR rats may contribute to other neurophysiological differences, such as changes in mGluR dependent LTD. Other studies have demonstrated enhanced mGluR dependent LTD in young, congenitally learned helpless rats (Pignatelli et al, ) and after acute treatment with corticosterone (Chaouloff, Hemar, & Manzoni, ), suggesting high mGluR receptor activation in animals with more depressive‐like behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations in these genes could potentially contribute to the observed HR/LR neurophysiological differences and/or may be involved in known behavioral differences. For instance, recent studies have associated increased expression of GRM5 with positive stress coping and resilience (Piers et al, ; Sun et al, ), so it is conceivable that HR rats' increased GRM5 levels relative to LRs may be associated with their proactive coping styles (Cohen et al, ). Additionally, the increased GRM5 levels in HR rats may contribute to other neurophysiological differences, such as changes in mGluR dependent LTD. Other studies have demonstrated enhanced mGluR dependent LTD in young, congenitally learned helpless rats (Pignatelli et al, ) and after acute treatment with corticosterone (Chaouloff, Hemar, & Manzoni, ), suggesting high mGluR receptor activation in animals with more depressive‐like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…These observed HR/LR differences in coping during the active avoidance task are consistent with several previous observations of disparate HR versus LR stress coping style. HR rats generally display a proactive response to stress, such as low immobility in the FST (Clinton et al, ; Cohen et al, ; Garcia‐Fuster et al, ; Glover et al, ; Stedenfeld et al, ), high aggression in the resident‐intruder test (Kerman et al, ), and high levels of probe burying behavior in the defensive burying task (Cohen et al, ). LR rats, on the other hand, consistently display “reactive coping” behavior, showing high FST immobility, low aggression, and high levels of freezing and almost no time burying the probe in the Defensive burying task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also show that stress-induced c-Fos activation in CeA may be predictive of coping strategy. For example, rats selectively bred for high freezing and low defensive burying behaviors when presented with a shock probe (low novelty responding rats; passive/reactive copers) show more CeA c-Fos activation following footshocks than their low freezing/high defensive burying counterparts (high novelty responding rats; active copers) [29]. Here, we found that Avoiders have more c-Fos+ cells in CeA than Non-Avoiders, Controls, and Single Stress rats not indexed for avoidance, and that the number of CeA c-Fos+ cells is positively correlated with avoidance of the predator odor-paired context (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our analyses on the basolateral amygdala (BLA) because of the known contribution of this region to fear learning and memory storage at remote time points [16][17][18][19] We recently demonstrated that exposure to a single acute stressor (120 minutes of restraint stress) induces a change in the molecular profile of the BLA, including differential expression of 18 miRNAs an entire month after stress [5]. Differential miRNA expression has also been reported in the serum of patients with PTSD [20] [21] and between rats selectively bred for high or low stress reactivity [22]. The behavioral consequences of stress exposure have also been linked to miRNA function in the amygdala in several reports.…”
Section: Introductionmentioning
confidence: 99%